American Indian and Alaska Native Enrollment in Clinical Studies in the National Institutes of Health's Intramural Research Program. Issue 3 (21st May 2021) - Vigil, Deionna; Sinaii, Ninet; Karp, Barbara
ABSTRACT: Clinical studies conducted by the National Institutes of Health's Intramural Research Program (NIH‐IRP) provide eligible individuals with access to innovative research treatments that may not otherwise be available. The NIH‐IRP's mission is to include all Americans, including American Indians and Alaska Natives, in its clinical research. This study is the first to provide data about inclusion of American Indians/Alaska Natives in NIH‐IRP clinical studies. We analyzed data from the more than 1, 800 NIH‐IRP protocols active in 2014 and 2017. We found that the absolute number of American Indian/Alaska Native enrollees increased between 2014 and 2017 but remained at 1% of all participants, a disproportionately low level. The number of clinical studies that enrolled American Indian/Alaska Native individuals similarly did not change. NIH efforts to expand participation of American Indians/Alaska Natives in clinical studies has often focused on research within their communities or on health needs specific to these groups. Those efforts should expand to include processes and protections for the proportionate and ethical inclusion of American Indians and Alaska Natives who individually enroll in studies that are not specific to American Indians, Alaska Natives, or their tribal nations.